From Digital Content to Corporate Brand Legitimacy: Transmedia Storytelling and Corporate Identity Mix in Grindboys - Rizky, Ega; Bilowo, Yusuf Bagas (Jurnal Indonesia Sosial Sains, 2026)
The rapid expansion of digital media has reshaped corporate communication, enabling non-traditional actors to evolve into organizational entities with recognizable identities and legitimacy claims. This article examines the transformation of Grindboys from a digital content creator collective into a community-based corporate brand within Indonesia’s contemporary creative industry, focusing on how transmedia storytelling and the corporate identity mix function as strategies for constructing collective identity and brand legitimacy. Grindboys develops narratives centered on friendship, everyday experiences, and shared cultural values across digital platforms such as YouTube, Instagram, and TikTok, which are extended into physical spaces (Warkopolim) and commercial expressions through merchandise. The findings indicate that Grindboys develops narratives centered on friendship, everyday experiences, and shared cultural values across digital platforms, which are extended into physical spaces and commercial expressions through merchandise. The integration of cross-media narratives with the symbolic, communicative, and behavioral dimensions of corporate identity produces a coherent and immersive brand experience, positioning audiences as active stakeholders in meaning-making and contributing to the sustainability of brand legitimacy. This study concludes that brand legitimacy can be formed discursively through repetitive, consistent, and distributed communication practices across media, rather than through formal institutional claims. The theoretical contribution lies in integrating transmedia storytelling and corporate identity mix frameworks in the context of community-based creative entities, while the practical contribution offers strategic guidance for creative industry practitioners in designing narrative-consistent, cross-media communication strategies.